Understanding pedestrian stressors and mitigators : a qualitative approach (2021)
the purpose of this research is to explore the factors that generate and mitigate stress for pedestrians in the streets of Bogotá from a qualitative approach. This is useful to define a concept of value, from the pedestrians? perspective, that they expect when walking down the streets. The approach gives results that relate directly with the first basic principle of the LEAN management, identifying value. This will be the first step in developing a guide for urban planning for pedestrians based on their stress. Then, the urban planning should increase stress mitigators and reduce stress intensifiers, all derived from users? expectations. What remains of this document is organized as follows: a literature review, the research methodology, results, discussion and finally a conclusion